“CUCI OTAK” PENANGGUNG PAJAK (STUDI PADA JURUSITA PAJAK KPP PRATAMA SURABAYA WONOCOLO) - Dewi Prastiwi (Universitas Teuku Umar, 2018)
Abstract: Hostage or Gjzeling is one tax collection efforts to penanggung pajak in certain places within a maximum period of 6 (six) months from the tax insurer placed in the hostage-taking and can be extended for ever 6 (six) months. Many of the constraints faced by jurusita pajak in the line of duty gijzeling, this study aims to explore ways gijzeling using a qualitative approach or non-positivistic with interpretive paradigm in approaching the true reality. The result showed that the efforts made for the success of jurusita pajak in gizjeling process is to: 1) believes that the process gijzeling a law enforcement efforts, the process of education to taxpayers, as well as carry out the mandate of the State to save the state money; 2) manage the conflict with tax insurer with a hang rule to the taxpayer, neutral, professional, and uphold integrity; 3) uploading awareness by downloading